The Th17/Treg Immune Imbalance in Ulcerative Colitis Disease in a Chinese Han Population - Yang Gong; Yifan Lin; Ning Zhao; Xiaojuan He; Aiping Lu; Wei Wei; Miao Jiang (Hindawi Limited, 2016)
Objective. To investigate the Th17/Treg immune balance in the ulcerative colitis (UC) patients in a Chinese Han population. Methods. Ninety UC patients and 30 healthy subjects were enrolled. The serum IL-17 and TGF-β1 levels of these participants were measured with ELISA; the percentage of Th17 and Treg cells in peripheral blood was determined with flow cytometry. Results. In UC patients, the levels of IL-17 and Th17 were significantly higher compared with healthy subjects; the percentage of Th17 and IL-17 level in moderate and severe subgroup was significantly higher than in mild subgroup; a positive correlation existed between these two indexes and clinical activity index and endoscopic evaluation. TGF-β1 level and Treg cells in UC patients were lower than healthy subjects. TGF-β1 level in moderate and severe subgroup was lower than in mild subgroup. There was a negative linear correlation between Treg cells and clinical activity index, endoscopic evaluation. A positive correlation was detected between Treg cells and TGF-β1 level. Conclusions. Th17/Treg immune imbalance might play a crucial role in the development of UC. To induce the production of Treg cells and TGF-β1, inhibit the level of Th17 and IL-17, and thus recover the Th17/Treg immune balance might imply new therapeutic targets in UC management.